2014
DOI: 10.1620/tjem.232.35
|View full text |Cite
|
Sign up to set email alerts
|

The Perception and Experience of Gender-Based Discrimination Related to Professional Advancement among Japanese Physicians

Abstract: Previous studies from the US have found that female physicians often experience gender-based discrimination related to professional advancement. In Japan, female physicians are underrepresented in leadership positions but little is known about the prevalence of gender discrimination. We investigated the perception and prevalence of gender-based career obstacles and discrimination among Japanese physicians. The study was based on surveys of alumnae from 13 medical schools and alumni from 3 medical schools. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 20 publications
5
18
2
Order By: Relevance
“…Gender inequality represents a common unfairness in the workplace and our previous study reported that women who perceived gender inequality were more likely to give up pursuing a career and instead switch to part-time labour from full-time work12 ) . Although our previous studies12, 14 ) related to gender inequality at work had not specifically investigated participants’ psychological response to gender inequality, the results of the present study may suggest that in a workplace where women negatively perceive organizational climate with gender equity, women may perceive psychological distress. Furthermore, it should be noted that the present study also suggested that when women perceived organizational climate for gender equality at higher degrees, women might perceive less psychological distress.…”
Section: Discussioncontrasting
confidence: 71%
“…Gender inequality represents a common unfairness in the workplace and our previous study reported that women who perceived gender inequality were more likely to give up pursuing a career and instead switch to part-time labour from full-time work12 ) . Although our previous studies12, 14 ) related to gender inequality at work had not specifically investigated participants’ psychological response to gender inequality, the results of the present study may suggest that in a workplace where women negatively perceive organizational climate with gender equity, women may perceive psychological distress. Furthermore, it should be noted that the present study also suggested that when women perceived organizational climate for gender equality at higher degrees, women might perceive less psychological distress.…”
Section: Discussioncontrasting
confidence: 71%
“…After categorization by sex, this result was also found for female physicians. The previous study showed female physicians older than 40 were more likely to experience gender discrimination compared with younger women (Yasukawa, 2014). However in this study, female physicians in younger generations were more likely to show the openness towards improving gender role attitudes.…”
Section: Discussioncontrasting
confidence: 68%
“…However, she did mention that feeling of being discriminated as a woman in her job in a former non-European destination country many times during the interview, explaining that it is tough to work as a female (and single) physician surrounded by mostly men. That view is reflected by other studies for example concerning gender-based discrimination of female physicians relating to career advancement possibilities in the US or Japan [68] and in general exclusion of female physicians from power structures of medicine [69] or sexual harassment against women working in the medical field [70]. …”
Section: Resultsmentioning
confidence: 92%
“…The experiences of our respondents are a reflection of power relations based on gender. The physician sector in many countries is still male dominated and women are often marginalized when they decide to go into a profession like medicine [68, 70]. It is however noteworthy that there are positive developments and that in some countries there is a gender balance in medical schools and some specialties (e.g.…”
Section: Discussionmentioning
confidence: 99%